The vocative style in Arabic and Indonesian languages: A contrastive analytical study - Fithri, Chusna Nazilatul; Maskud, Maskud; Maulana, Asep (Abjadia : International Journal of Education, 2025)
The call (an-nida) is a fundamental form of human communication that signifies the need for interaction among individuals. Calling methods vary between languages, reflecting diverse cultural values and impacting language understanding and cross-cultural interaction. The researcher chose qualitative research and followed the descriptive-analytical approach, using the introspective approach in data collection. When analyzing the data, she relied on the comparative analysis method. One of the key findings of this research is that the call in Arabic and Indonesian shows both similarities and differences. Each language uses tools for calling, including a common tool for general calls, which is "يا" in Arabic and "[Wahai]" in Indonesian. These tools may be omitted from speech for brevity. In terms of grammatical analysis, the tools affect the addressees in Arabic, while they do not affect the addressees in Indonesian. Arabic distinguishes between the intended and unintended vocatives through diacritical marks, while Indonesian does not make this distinction, considering the circumstances and keeping the word in its original form